2018
DOI: 10.1186/s11658-018-0084-2
|View full text |Cite
|
Sign up to set email alerts
|

Lycium barbarum polysaccharide protects HSF cells against ultraviolet-induced damage through the activation of Nrf2

Abstract: BackgroundLycium barbarum polysaccharide (LBP) is considered an antioxidant agent. NF-E2-related factor-2 (Nrf2) is an important regulator for protection against UV damage. In this study, we verified the performance of LBP and the correlation between LBP and Nrf2.MethodsHSF cells were treated with LBP to determine dose and time dependencies. An antioxidant response element (ARE) reporter was designed to monitor the activity of the Nrf2 antioxidant pathway.ResultsFor HSF cells, the optimal LBP treatment was 300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…Previous studies have reported that activation of Nrf2 and its downstream gene HO-1 plays an antioxidant role in many cell lines [12]. In the last years, many researchers have focused on the antioxidant effects of natural products and their extracts [27][28][29]. In our study, interestingly, both nNrf2 and HO-1 levels increased rapidly after asiaticoside treatment for 3-6 h. After treatment with various doses of asiaticoside (50-150 μM) for 6 h, both T-Nrf2 and HO-1 levels were significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that activation of Nrf2 and its downstream gene HO-1 plays an antioxidant role in many cell lines [12]. In the last years, many researchers have focused on the antioxidant effects of natural products and their extracts [27][28][29]. In our study, interestingly, both nNrf2 and HO-1 levels increased rapidly after asiaticoside treatment for 3-6 h. After treatment with various doses of asiaticoside (50-150 μM) for 6 h, both T-Nrf2 and HO-1 levels were significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant effects of LBP were already demonstrated. Two in vitro studies 39,40 have shown that the LBP fraction can partially protect against UVR‐induced photodamage through activation of the nuclear factor E2‐related factor 2 (Nrf2/ARE) pathway, thereby scavenging reactive oxygen species (ROS), reducing DNA damage and suppressing UVR‐induced p38 MAPK pathway. The treatment with LBP also increased the levels of antioxidant defenses, such as superoxide dismutase (SOD) and glutathione peroxidase (GSP‐PX), reaffirming the antioxidant potential of this fraction 39,40 …”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant activity, antitumor properties, immune regulation, and neuroprotective effects of LBPs were explored in in vitro and in vivo models. Besides this, LBPs also have other biological activities, such as protecting the liver from hepatotoxicity [122], alleviating dry-eye disease [123], eliciting antidiabetic effects [124], increasing cell abilities, decreasing cell morphologic impairment, protecting against ultraviolet-induced damage [122], and alleviating CCl4-induced liver fibrosis [125]. As bioactive constituents, LBPs exhibit various biological functions and show potential benefits to people’s health.…”
Section: Biological Function Of Lbpsmentioning
confidence: 99%